2019
DOI: 10.1177/0954407019841218
|View full text |Cite
|
Sign up to set email alerts
|

From fundamental study to practical application of kerosene in compression ignition engines: An experimental and modeling review

Abstract: The use of kerosene in direct injection compression ignition engines is fundamentally due to the introduction of the Single Fuel Concept. As conventional direct injection compression ignition diesel engines are made specifically to use diesel fuel, the usage of kerosene will affect engine emissions and performance due to differences between the fuel properties of kerosene and diesel. As a result, in order for kerosene to be properly and efficiently used in diesel engines, it is needful for the scientific commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 191 publications
(764 reference statements)
0
3
0
Order By: Relevance
“…This is mainly attributed to more accumulation of fuel in combustion chamber before ignition caused by the increased ignition delay when fueled with Jet A-1. Besides, another reason is that the Jet A-1 which has a lower viscosity than diesel (shown in Table 3) undergoes atomization more easily and therefore experiences a shorter penetration with a wider spray angle, which can be deduced from the authors' previous spray study of Jet fuel [26,28,29]. As shown in Fig.…”
Section: Combustion and Gas Emissions Characteristics Of Jet A-1mentioning
confidence: 97%
“…This is mainly attributed to more accumulation of fuel in combustion chamber before ignition caused by the increased ignition delay when fueled with Jet A-1. Besides, another reason is that the Jet A-1 which has a lower viscosity than diesel (shown in Table 3) undergoes atomization more easily and therefore experiences a shorter penetration with a wider spray angle, which can be deduced from the authors' previous spray study of Jet fuel [26,28,29]. As shown in Fig.…”
Section: Combustion and Gas Emissions Characteristics Of Jet A-1mentioning
confidence: 97%
“…Kerosene, an intermediate component of WDF, is much easier to ignite than gasoline during the compression process, while has better fuel-air mixing characteristics compared with diesel. 24,25 That is, kerosene combines the preferable physicochemical properties of diesel and gasoline to a certain extent, and Chen et al 26,27 suggested that kerosene could be considered as a suitable fuel for a compression ignition engine without significant modifications. Bergstrand 28 also pointed out that considering the potential to expand the operating area and the market availability, kerosene has the possibility to be a suitable LTC fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Kerosene use in direct injection diesel engines started at the end of 1980s when by NATO nations introduced the single fuel concept, who decided to use a specific fuel to supply all land based military aircraft and vehicles that aimed at simplifying the logistic chain for petroleum by-products [15,16]. F-34 (JP-8) military jet kerosene was selected as the single fuel; it has the same specifications of the F-35 (Jet A), except for those that are related to the use of additives that are used to inhibit system icing and to face with corrosion and thermal stability [17].…”
Section: Introductionmentioning
confidence: 99%